Efficacy and Safety of Suprachoroidal Triamcinolone Acetonide in Cases of Resistant Diabetic Macular Edema - Yasir Ahmad, Saud Ul Hassan Memon, Shahid Anwar Bhatti, Faisal Nawaz, Waleed Ahmad, Maria Saleem (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Patients with diabetes are at risk of losing their vision due to diabetic macular edema (DME). Symptoms of diabetic macular edema occur as fluid leaks from retinal vessels into the surrounding neural retina due to hypoglycemia-induced damage to the blood-retina barrier. The current study aimed to assess the safety and efficacy of suprachoroidal triamcinolone acetonide in resistant diabetic macular edema cases. Patients and Methods: This interventional case series was carried out on 32 diabetic macular edema cases in the Department of Ophthalmology, Hayatabad Medical Complex, Peshawar during the period from April 2019 to September 2019. All the patients above 16 years of age with Type-1 DM or Type-2 DM were enrolled in this study. Intraocular Pressure (IOP), Baseline Best Corrected Visual Acuity (BCVA), and Central Subfield Thickness (CST) were determined and recorded. Post-SCTA follow-up was done in one and three months. During follow-up, the measured clinical factors were noted and analyzed in SPSS version 26. Results: Of the total 32 diabetic macular edema cases, 15 (46.9%) were male and 17 (53.1%) were females. The overall mean age was 48.64 ± 8.72 years. The frequency of prior injections received were 6.2 with maximum 12 and minimum four. CST pre-injection mean value was 612.8 ± 198.3 um and CST post-injection mean value at one and three months was 308.6± 62.6 um and 302.72± 58.64 um respectively. Statistical significance was found in pre and post one-month CST injections. The BCVA pre-injection and post-injection mean value at one and three months was 0.8 ± 0.19 and 0.49 ± 0.29 and 0.39 ± 0.20 respectively. At the one and three months post injection, there was statistical significance for both pre and post injection CST. A mean IOP of 12.32 mmHg was recorded pre-injection. Previously, 14.82 mmHg and 14.48 mmHg of intraocular pressure were recorded respectively after one and three months of injection. Conclusion: The present study found that Triamcinolone Acetonide (TA) was administered for anatomical and functional improvement. OCT macular thickness can be improved and refractory diabetic macular edema can be reduced using SCT. Keywords: Resistant diabetic macular edema, Efficacy, Suprachoroidal Triamcinolone